Five golden rules : great theories of 20th-century mathematics and why they matter - Casti, J. L. (New York : Wiley & Sons, 1996)
Examines the discoveries of five of the most important mathematical formulas of this century and their implications in our lives.
Includes bibliographical references (p. 217-225) and index.
Choice.
Library Journal.
Adult.
Adult
Keywords: Mathematics -- Popular works; Mathematics